A COMPARATIVE ANALYSIS OF JOB ATTITUDES BETWEEN FULL-TIME AND OUTSOURCING EMPLOYEES AT PT. TELKOM AKSES IN MANADO - Siahaan, Sika E. K; Kalangi, Josep B.; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: This study aims to examine whether there are significant differences in job attitudes between full-time employees and outsourcing employees. This study took the place at PT. Telkom Akses in Manado. This study is a quantitative research by distributing questionnaires using Likert Scale. The samples used are full-time employees and outsourcing employees at PT. Telkom Akses in Manado with the number of samples divided into two parts, namely 30 samples of full-time employees and 30 samples of outsourcing employees with a total of 60 samples. Validity test is used in this research using the Pearson Product Moment. Reliability test is used in this research using the Alpha Cronbach. Normality test is used in this research using Kolmogorov-Smirnov Test. Technical analysis used in this research is Independent Sample t-test, where it uses to compare two independent variables. This research is a comparative test which then gets result that there are significant differences in job attitudes between full-time employees and outsourcing employees at PT. Telkom Akses in Manado. From this research the researcher suggest that both company and empoyees must pay more attention to the agreement.Â Keywords:job attitudes, full-time employees, outsourcing employees